2021
DOI: 10.1136/annrheumdis-2021-eular.2330
|View full text |Cite
|
Sign up to set email alerts
|

Pos0540 sexual Dysfunction in Male Patients With Rheumatic Diseases

Abstract: Background:Sexual health is an essential element of overall health and well-being. Rheumatic diseases may affect sexual functioning in many ways related to pain, fatigue, stiffness, functional impairment, depression, anxiety, negative body image, reduced libido, hormonal imbalance and drug treatment. However, these issues are rarely addressed in clinical practice.Objectives:The aim of this study was to evaluate sexual function in a cohort of men with rheumatic disease compared to healthy controls.Methods:This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…16 In a Romanian study, with cohort of 60 patients, having mean age was 45.26 (7.8) years with various autoimmune rheumatic disease (rheumatoid arthritis (RA) -17%, cases), 21,66% of the patients reported erectile dysfunction (ED) in comparison with only 8,33% in the control group (p=0.009) in comparison our cohort was very young in age. 17 Danish study results showed some alarming statistics that; majority of patients with RA (93.5% of women and 85.5% of men) had not discussed sexual issues with a healthcare professional during the last five years. Of all, 32.5% wished that their health care provider must discuss about sexual health.…”
Section: Resultsmentioning
confidence: 99%
“…16 In a Romanian study, with cohort of 60 patients, having mean age was 45.26 (7.8) years with various autoimmune rheumatic disease (rheumatoid arthritis (RA) -17%, cases), 21,66% of the patients reported erectile dysfunction (ED) in comparison with only 8,33% in the control group (p=0.009) in comparison our cohort was very young in age. 17 Danish study results showed some alarming statistics that; majority of patients with RA (93.5% of women and 85.5% of men) had not discussed sexual issues with a healthcare professional during the last five years. Of all, 32.5% wished that their health care provider must discuss about sexual health.…”
Section: Resultsmentioning
confidence: 99%